A Large Isolated Pleural Effusion in the Right Hemithorax as an Unusual Manifestation Following IVF - Alnassar, Abdulaziz (International Journal of Innovative Research in Medical Science, 2023)
Background: Ovarian hyperstimulation syndrome (OHSS) is a serious iatrogenic complication of ovulation induction therapy. I hereby present a rare case of a large, isolated right-sided pleural effusion causing respiratory compromise following IVF. The clinical presentation of abdominal ascites is known to be common in OHSS, with isolated pleural effusions being a rare finding. Case presentation: The reported case is a rare example of an isolated pleural effusion in a 36-year-old lady with polycystic ovarian syndrome (PCOS) and ongoing sessions of IVF due to infertility. The patient was hospitalized due to shortness of breath. A chest x-ray was performed and revealed a large pleural effusion in the right hemithorax. Ultrasound-guided thoracentesis was safely performed without complications. Conclusions: I hereby present a rare clinical manifestation of OHSS presenting with a large isolated pleural effusion. Patients being treated for infertility with ovulation induction should be assessed and monitored frequently for the prevention of developing OHSS.